Differential Settlement of Intersecting Buildings in an Offshore Reclamation Project. (20th March 2019) - Su, Jing-Bo; Yu, Zheng-yang; Lv, Ya-Ru; Zhu, Yi-Huan; Wang, Hua-Qing
Abstract : This paper addresses the problem of open gaps caused by differential settlement in the process of constructing sluice buildings in soft soil beach areas, combined with the construction of sluice and supporting facilities in a reclamation project. First, the change rules for the shear strength and compression modulus of soft soil under different consolidation degrees are studied by theoretical analysis. Then, an interaction model for soft soil and pile soil is established using the geotechnical finite element analysis software MIDAS/GTS NX. The change rules for the vertical and horizontal ultimate bearing capacities of a single pile with the degree of soil consolidation are studied. On this basis, a three-dimensional numerical analysis model of drainage sluice, seawall, cofferdam, and foundation soil is established, and the relationship between the degree of soil consolidation and the development of structural gaps caused by differential settlement is obtained. The research results show that the bearing capacity of a single pile increases greatly with the consolidation of soil around the pile and that the gap width between the structures in the project decreases with increasing consolidation. This paper provides a theoretical basis for the prediction of pile bearing capacity in the preliminary design stage and the evaluation and calculation of differential settlement of intersecting buildings in soft soil beach areas.